Effectiveness of transcatheter edge-to-edge repair for atrial secondary mitral regurgitation. (3rd October 2022) - Tanaka, T; Sugiura, A; Oeztuerk, C; Vogelhuber, J; Tabata, N; Wilde, N; Zimmer, S; Nickenig, G; Weber, M
Abstract: Background: Atrial secondary mitral regurgitation (ASMR) is a subtype of SMR that is characterized by normal left ventricular (LV) function, an enlarged left atrium and mitral annulus, and flattened leaflets. This anatomical feature is different from ventricular SMR (VSMR) and might therefore impact the procedural results of transcatheter edge-to-edge repair (TEER). The effectiveness and durability of TEER in patients with ASMR has not yet been well-studied. Purpose: This study aimed to investigate the effectiveness of TEER and anatomical characteristics related to optimal MR reduction in patients with ASMR. Methods: We retrospectively analyzed consecutive patients who underwent MitraClip at our institution. ASMR was defined as cases that met all of the following criteria: 1) normal mitral leaflets without organic disorder, 2) LV ejection fraction >50%, and 3) absence of LV enlargement and segmental abnormality. The primary outcome measure was MR reduction to ≤1+, and its predictors were explored in a logistic regression analysis. Leaflet-to-annulus index (LAI) was measured using the mid-esophageal long-axis view in the A2-P2 segment as follows: (anterior leaflet length + posterior leaflet length) / anteroposterior length of the mitral annulus. Results: Among 415 patients with SMR, 118 patients met the criteria for ASMR (mean age: 80±8 years; male: 39.8%) (Figure 1). Patients with ASMR had a larger mitral annulus diameter, shorter mobile posterior leaflet length, and smaller coaptation depth compared to those with VSMR. The technical success rate was 90.7%, and the MR reduction to ≤1+ after TEER was achieved in 94 (79.7%) patients with ASMR, which was comparable with VSMR. The in-hospital mortality rate was 2.5%. In multivariable logistic analysis, a large left-atrial (LA) volume index and a low LAI were associated with a lower rate of MR reduction to ≤1+ after TEER for ASMR (odds ratio [OR]: 0.98; 95% confidence interval [CI]: 0.97–0.99, and OR per 0.1 increase: 1.98; 95% CI: 1.13–3.45, respectively). The combined assessment of the LA volume index and LAI stratified the risk of residual MR ≥2+ after TEER (Figure 2). In addition, the use of a newer generation of the MitraClip systems (NTR/XTR or G4 systems) was associated with a higher rate of MR reduction to ≤1+ compared to older generations (OR: 4.65; 95% CI: 1.67–13.00). Conclusions: TEER with the MitraClip system achieved a high rate of MR reduction to ≤1+ in patients with ASMR. Furthermore, the new generations of the MitraClip system may provide a more effective reduction in ASMR. Although our findings suggest that TEER with the MitraClip system is a safe and feasible approach in patients with ASMR, the combined assessment of the LA volume index and LAI might be useful to refine the device selection for transcatheter mitral valve treatment in this subgroup of SMR patients. Funding Acknowledgement: Type of funding sources: None.